Pengembangan Soal Matematika Model PISA Konteks Kain Cual Bangka Belitung - Yudi Yunika Putra; Rajab Vebrian (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2019)
This study aims to Produce PISA model mathematical problems context kain cual Bangka Belitung that meets valid, practical, and potential effect on students abilities mathematical literacy based on Basic Mathematics Ability. The subject of this research is students SMP Negeri 5 Pangkalpinang class IX.A is amounts 35 student. The research method uses design research type development study. Data were analyzed description based on criteria literacy mathematic ability based on Basic Mathematics Ability. Result this research is obtained a set of PISA mathematical problems Context kain cual Bangka Belitung is valid, practical, and potential effect on students abilities mathematical literacy. Valid obtained at stage expert review and one to one practicality is known in stages small group, and ability mathematic literacy based result analysis the answer students and questionnaire on field test stage. Based the result analysis is obtained developed problems have a potential effect on mathematical literacy abilities namely bring up the Basic Mathematical Ability.